Type 2 Diabetes in Urban and Rural Districts in Korea: Factors Associated with Prevalence Difference - Lee, Hye Young; Won, Jong Chul; Kang, Yoon Jung; Yoon, Sook Hee; Choi, Eun Ok; Bae, Jeong Yee; Sung, Mi Hae; Kim, Hye-Ryoung; Yang, Jin Hyang; Oh, Jina; Lee, Yun Mi; Park, Nam Hee; et al. (Journal of Korean medical science, 2010)
The purpose of this study was to examine the urban-rural differences in the prevalence and associated factors with type 2 diabetes mellitus (T2DM) in Korean adults. A total of 1,060 adults >30 yr of age from urban (189 males and 331 females) and rural districts (219 males and 321 females) were recruited. Anthropometric measures, blood pressure, lipid profiles, and fasting and 2-hr after 75-g oral glucose load blood glucose were obtained. The crude- and age-standardized prevalence of T2DM was 15.4% and 14.5%, and 11.7% and 8.6% in urban and rural districts, respectively. Diabetic subjects were older and obese, and had a higher triglyceride level, and systolic blood pressure compared to non-diabetes in both population. Multivariate regression analysis revealed that older age, high triglyceride levels, central obesity, and hypertension were significantly associated with T2DM in both areas. Low monthly incomes were significantly associated with T2DM in urban population, while a family history of T2DM was significantly associated with T2DM in rural area. T2DM is more prevalent in urban than in rural population, and low economic status or genetic factor is differently associated with T2DM in both population, respectively.